COMMON SIZE ANALYSIS OF THE FINANCIAL RESILIENCE OF SHARIA MICROFINANCE INSTITUTIONS (LKMS) IN FACING GLOBAL ECONOMIC VOLATILITY - SINGKHALA, SURASIT (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyze the level of financial resilience of Islamic Microfinance Institutions (LKMS) in facing increasingly uncertain global economic dynamics. Using a common size analysis approach, this study seeks to evaluate the ability of LKMS to maintain the efficiency and sustainability of its financial structures amidst external pressures such as inflation, exchange rate depreciation, and slowing economic growth. In the context of financial inclusion in Indonesia, LKMS plays a vital role as a provider of sharia-based alternative financial services and reaches the grassroots community. This study uses a qualitative method based on case studies with secondary data from officially published LKMS financial reports. The analysis results indicate that most LKMS exhibit adaptive patterns through strengthening liquid assets, diversifying revenue, operational cost efficiency, and increasing risk reserves. Thus, it can be concluded that LKMS has sufficient financial resilience to survive amidst global economic uncertainty. The implications of this study can serve as a reference for LKMS managers, regulators, and academics in strengthening sustainable Islamic microfinance governance.